2001
DOI: 10.1128/iai.69.2.832-837.2001
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide-Induced Gelatinase Granule Mobilization Primes Neutrophils for Activation by Galectin-3 and Formylmethionyl-Leu-Phe

Abstract: We have earlier shown that galectin-3, a lactose-binding mammalian lectin that is secreted from activated macrophages, basophils, and mast cells, induces activation of the NADPH oxidase in exudated but not in peripheral blood neutrophils (A. Karlsson, P. Follin, H. Leffler, and C. Dahlgren, Blood 91:3430-3438, 1998). The alteration in responsiveness occurring during extravasation correlated with mobilization of the gelatinase and/or specific granules to the cell surface, indicating a role for mobilizable galec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
77
1
6

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 85 publications
(88 citation statements)
references
References 46 publications
3
77
1
6
Order By: Relevance
“…Others and we have shown the ability of galectin-3 to activate cells such as neutrophils to induce the production of reactive oxygen species, IL-8 and L-selectin shedding (43,44,61,67). According to the group of Raz, galectin-3 also has the ability to induce endothelial cell morphogenesis and angiogenesis (68).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Others and we have shown the ability of galectin-3 to activate cells such as neutrophils to induce the production of reactive oxygen species, IL-8 and L-selectin shedding (43,44,61,67). According to the group of Raz, galectin-3 also has the ability to induce endothelial cell morphogenesis and angiogenesis (68).…”
Section: Discussionmentioning
confidence: 99%
“…Through this interaction, it has been shown to induce IL-1 production by monocytes (36,42), and L-selectin shedding (43), production of IL-8 (43), and reactive oxygen intermediates by neutrophils (44,45). In addition, others and we have demonstrated that soluble galectin-3 can act as an adhesion molecule for neutrophils through ligand cross-linking (29,46,47).…”
mentioning
confidence: 99%
“…Interacting with Neutrophils-Upon binding to neutrophils, galectin-3 induces various activities such as production of interleukin 8 (12), L-selectin shedding (12), reactive oxidative intermediate production (26,27,46), and adhesion to the extracellular matrix and endothelial cells (13,14). These activities are not induced in the presence of galectin-3 antagonists, which block the binding, nor by the truncated form of galectin-3, which lacks the N-terminal domain.…”
Section: Detection Of Fret Signal From Galectin-3-tg1-alexamentioning
confidence: 99%
“…The molecular basis for recognition and signaling in response to chemoattractants such as C5a, platelet-activating factor (PAF), 1 interleukin-8 (IL-8), and formylated peptides is the binding to and activation of specific receptors (2), resulting in directed migration, granule mobilization, and activation of the neutrophil NADPH-oxidase. The chemoattractant receptors can be recruited to the cell surface from intracellular storage organelles (3)(4)(5), but the responses are not only influenced by the degree of receptor exposure on the cell surface but also by the survival time of its activated state and the time required for termination of the signals from the occupied receptor (6).…”
mentioning
confidence: 99%